MENINGKATKAN PRESTASI BELAJAR MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS PADA MATA KULIAH SPEAKING V MELALUI LESSON STUDY - Misnar Misnar (Jurnal Pendidikan Almuslim, 2016)
This article aimed at improving the students’ ability in mastering speaking V. This activity was done through a mechanism of in-service training, focused on an attempting to the lecture’s empower  according to their capacity and the problem faced. Lesson study is a model to improve the lectures through  and teaching analysis collaborative continuous based on colleagueship principles and mutual learning to build community learning. Lesson study was chosen and implemented to improve the students’ ability in mastering speaking V because it was considered as an  effective strategy  to improve teaching and learning quality in the classroom. This was also due to the fact that lesson study was developed and conducted under a shared profesiona-lism knowledge based on best practices and learning outcomes. There are four steps in conducting lesson study, such as (1) to plan research lesson, (2) to conduct and observe teaching and learning activities, (3) to analyze and discuss observation results, and (4) to make a reflection and revision. The students’ achievement in the fourth cycle was 80.16. Although, the students’ respond was 9.13%, it is mean that the students very interested in learning through lesson study. In conclusion, lesson study improved the students ability in mastering speaking V.    Key words : Ability, speaking V, lesson study